Develoment of an assessment method for hazardous substances value in automotive components for supporting green manufacturing - Martawirya, Yuwana Yatna (ASEAN engineering journal)
This aim of this research is to develop an assessment method for hazardous substances value in automotive components for supporting green manufacturing. Basically, the green manufacturing focuses on reducing environmental risks and impacts of industrial activities through elimination of resource waste, pollution and use of material containing hazardous substances. In this research, the method will be used to assess the hazardous substances contained in automotive components quantitatively. Based on the values, the hazard level of components could be compared relatively. This research has retrieved hazardous substances information from the Material Safety Data Sheet(MSDS) of the component. After that the hazardous substances were assessed based on the Hazardous Materials Identification System (HMIS). Furthermore, the information would be processed using a weighting method to obtain a single value. This research has assessed several automotive components by using the method as case studies. The results of assessments are brake pad 6.6, brake pad with asbestos 7.6, brake shoe 7.0, brake shoes with asbestos 13.2, clutch disc 9.2, and clutch disc with asbestos 8.6.